Relationship between Blood Lead Levels and Nitric Oxide (NO) Levels in Preeclampsia - Rina Oktaviana; Yusrawati Yusrawati; Arni Amir (Indonesian Journal of Obstetrics & Gynecology Science, 2022)
Objective: This study aims to determine the relationship between blood lead levels and NO levels in preeclampsia.Methods: This research applied analytical survey research with a cross-sectional design. Moreover, the samples were 99 pregnant women, 33 with normal pregnancies, 33 with preeclampsia living >10km from Semen Padang factory, and 33 with preeclampsia who lived ≤10km from Semen Padang factory. Spearman correlation test and logistic regression analysis is used for data analysis.Result: The result of this study shows that the blood lead level median in preeclampsia ≤10km is 26.23 g/dL, and the lead level median in preeclampsia >10km is 23.52 g/dL. Meanwhile, the NO level median in preeclampsia ≤10km is 22.50µmol/L and NO level median in preeclampsia >10km is 28.00µmol/L. There is a relationship between blood lead levels and NO levels in preeclampsia ≤10km, with r-value = -0.601 and p-value <0.001, in preeclampsia >10km, there is no relationship with p-value >0.500 and the strength of the correlation is fragile. In addition, the results of multivariate analysis of reduced levels of NO in preeclampsia with high blood lead levels are two times compared to preeclampsia with normal blood lead levels with 95% CI (0.652-6.362) after being controlled by distance of residence, smoking status and living environment variables.Conclusion: there is a relationship between blood lead levels and NO levels in preeclampsia.Hubungan Kadar Timbal dengan Kadar Nitric Oxide (NO) pada Ibu Hamil PreeklampsiaAbstrakTujuan: Penelitian ini bertujuan untuk mengetahui hubungan kadar timbal dengan kadar Nitric Oxide (NO)  pada ibu hamil preeklampsia. Metode: Penelitian ini merupakan penelitian survei analitik, dengan rancangan cross sectional. Sampel diteliti sebanyak 99 orang ibu hamil, 33 orang ibu hamil normal dan 33 orang preeklampsia yang tinggal yang tinggal radius >10km, dan 33 orang preeklampsia yang tinggal radius ≤10km. Kadar timbal diperiksa menggunakan metode AAS dan Kadar Nitric Oxide (NO)  diperiksa menggunakan metode ELISA. Analisis data menggunakan uji korelasi Spearman dan analisis regresi logistik.Hasil: Hasil penelitian ini median kadar timbal pada preeklampsia ≤10km adalah 26,23 µg/dL, dan median kadar timbal preeklampsia >10km adalah 23,52 µg/dL. Median kadar Nitric Oxide (NO)  preeklampsia ≤10km adalah 22,50µmol/L, median kadar Nitric Oxide (NO) preeklampsia >10km adalah 28,00µmol/L. Terdapat hubungan kadar timbal dengan kadar Nitric Oxide (NO) pada preeklampsia ≤10km, diperoleh nilai r = -0,601 dan nilai p < 0,001, pada preeklampsia  >10km tidak terdapat hubungan dengan nilai p > 0.500 dan kekuatan korelasi sangat lemah. Hasil analisis multivariat penurunan kadar Nitric Oxide (NO) preeclampsia yang memiliki kadar timbal tinggi adalah 2 kali dibandingkan ibu hamil preeclampsia dengan kadar timbal normal dengan 95% CI (0.652-6.362) setelah dikontrol variabel jarak tempat tinggal, status merokok dan lingkungan tempat tinggal.Kesimpulan: Terdapat hubungan kadar timbal dengan kadar Nitric Oxide (NO)  pada ibu hamil preeklampsia.Kata kunci: Timbal, Nitric Oxide, Preeklampsia